Accumulation of Oxidized Low-Density Lipoprotein in Psoriatic Skin and Changes of Plasma Lipid Levels in Psoriatic Patients - Nilgun Solak Tekin; Ishak Ozel Tekin; Figen Barut; Emine Yilmaz Sipahi (Mediators of Inflammation)
Background. Psoriasis is a chronic inflammatory skin disease characterized by an accelerated turnover of epidermal cells and an incomplete differentiation in epidermis with lesion. However, the exact etiology of psoriasis is unknown. Abnormalities in essential fatty acid metabolism, free radical generation, lipid peroxidation, and release of lymphokines have been proposed. Objective. Our purpose was to evaluate the plasma lipids and oxidized low-density lipoprotein accumulation in psoriatic skin lesion in order to ascertain the possible participation of oxidative stress and oxidative modification of lipids in pathogenesis of psoriasis. Methods. The study group included 84 patients with psoriasis, and 40 sex- and age-matched healthy volunteers. Blood lipid profile was determined. Psoriatic and nonlesional skin samples of psoriatic patients were evaluated for the presence of oxidized low-density lipoprotein by using an immune-fluorescent staining method. Results. The mean levels of lipids (total cholesterol, triglyceride, and LDL cholesterol) in patients with psoriasis were found to be significantly higher than those of healthy subjects. Psoriatic skins were shown positive oxidized low-density lipoprotein staining. There was no staining in nonlesional skin samples of the same individuals. Conclusion. Lipid peroxidation mediated by free radicals is believed to be one of the important causes of cell membrane destruction and cell damage. This study shows for the first time the accumulation of oxidized low-density lipoprotein in psoriatic skin lesion. We believe that accumulation of ox-LDL in psoriatic skin may have an important role in the immune-inflammatory events that result in progressive skin damage.